Sacred violence : African Christians and sectarian hatred in the age of Augustine - Shaw, Brent D. (Cambridge ; New York : Cambridge University Press, 2011)
"One route to understanding the nature of specifically religious violence is the study of past conflicts. Distinguished ancient historian Brent D. Shaw provides a new analysis of the intense sectarian battles between the Catholic and Donatist churches of North Africa in Late Antiquity, in which Augustine played a central role as Bishop of Hippo. The development and deployment of images of hatred, including that of the heretic, the pagan, and the Jew, and the modes by which these were most effectively employed, including the oral world of the sermon, were critical to promoting acts of violence. Shaw explores how the emerging ecclesiastical structures of the Christian Church, on one side, and those of the Roman imperial state, on the other, interacted to repress or excite violent action. Finally, the meaning and construction of the acts themselves, including the Western idea of suicide, are shown to emerge from the conflict itself"--
1. This terrible custom -- 2. Church of the traitors -- 3. A poisonous brood of vipers -- 4. Archives of memory -- 5. City of denial -- 6. Ravens feeding on death -- 7. Little foxes, evil women -- 8. Guardians of the people -- 9. In the house of discipline -- 10. Sing a new song -- 11. Kings of this world -- 12. We choose to stand -- 13. Athletes of death -- 14. Bad boys -- 15. Men of blood -- 16. Divine winds -- 17. So what? -- Appendix A. Bishops and bishoprics in Africa: the numbers -- Appendix B. Origins of the division: chronology -- Appendix C. The Catholic conference of 348 -- Appendix D. The Edict of Unity and the persecution of 347 -- Appendix E. The mission of Paul and Macarius -- Appendix F. Historical fictions: interpreting the circumcellions -- Appendix G. The archaeology of suicide -- Appendix H. African sermons.
Includes bibliographical references (p. 850-900) and index.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Christianity -- Africa -- History; Violence -- Religious aspects -- Christianity; Church history -- Primitive and early church, ca. 30-600.; Donatists; Africa, North -- Church history